Care for Newborns by Primipara Mothers in Developing Countries: Scooping Review - ova jayanti; Farida Kartini; Sri Ratnaningsih (Universitas 'Aisyiyah Yogyakarta, 2021)
Almost every parent feels the joy of welcoming their healthy baby. On the other hand, the presence of the baby also raises worry and sadness regarding his care. This Scoping Review aims to collect and map the literature on the care of newborns by primiparous mothers in developing countries. Review and group of literature based on the Arksey and O'Malley framework using 3 databases, namely Pubmed, Sciencedirect, Wiley, and Gray Literature from Google Scholar. Based on 7 articles included, it is known that the knowledge of primipara mothers in the country developed quite high. it was found that several traditional practices were not under WHO recommendations.